2016
DOI: 10.2116/analsci.32.413
|View full text |Cite
|
Sign up to set email alerts
|

Flow Injection Analysis of 5-(Hydroxymethyl)-2-furaldehyde in Honey by a Modified Winkler Method

Abstract: One of the quality indicators for honey is 5-(hydroxymethyl)-2-furaldehyde (HMF), which is formed during the heating or aging of honey. The International Honey Commission recommends three methods for the determination of HMF in honey: the Winkler method, the White method, and determination by HPLC. The Winkler method uses the carcinogenic substance p-toluidine, which is not in accordance with the principles of Green Chemistry. The present work describes the determination of HMF in honey by flow injection analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…All the articles studied showed concern with the waste generated and contributed to the SDG 12. Forty-eight evaluated articles proposed analytical methods that resulted in the reduction of waste generated [6 -53] seven studies presented techniques that did not require chemical products [54 -60] and nine studies suggested alteration of reagent / solvent for a similar less harmful to the environment and health [4, 19,26,30,44,[61][62][63][64].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the articles studied showed concern with the waste generated and contributed to the SDG 12. Forty-eight evaluated articles proposed analytical methods that resulted in the reduction of waste generated [6 -53] seven studies presented techniques that did not require chemical products [54 -60] and nine studies suggested alteration of reagent / solvent for a similar less harmful to the environment and health [4, 19,26,30,44,[61][62][63][64].…”
Section: Resultsmentioning
confidence: 99%
“…Brondi et al, 2013 [43] determined sulfate in water. The other works [4,19,26,44,51,61,62,64,65] reduce or replaced toxic reagents / solvents with other chemicals that perform the same function but are less harmful to the operator's health and the environment. De Prá Urio and Masini, 2017 [15] evaluated in their work the presence of two herbicides, Simazine and Atrazine, in rivers.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the colored product formed in the reaction involving PABA, BA, and HMF was described by Castoldi et al [33] and is illustrated in Fig. 1A.…”
Section: Determination Of Product Structurementioning
confidence: 92%
“…The reagent solution, described in the work of Castoldi et al [33], was based on the Winkler method for determination of HMF in honey samples [34]. This solution contained p-aminobenzoic acid (PABA), barbituric acid (BA), and hydrochloric acid (HCl).…”
Section: Reagent Solutionmentioning
confidence: 99%
See 1 more Smart Citation